Natural life cycle and rearing of Spodoptera frugiperda (Lepidoptera: Noctuidae) in the laboratory: Scientometric study and didactic scheme - Bentes, Vanessa dos Santos; Silva, Bruna Novais; Ribeiro, Taiã Mairon Peixoto; Paiva, Maykon Jhuly Martins de; Carvalho, Antonio Sérgio Silva de; Santos, Taides Tavares dos (Seven Editora, 2024)
Insects play a highly important role in the ecological field, especially playing a fundamental role in the pollination of flowering plants, an essential process for the preservation of life and biological diversity. Among the insects, there are those considered as pests. This is the case of Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctidae) also known as fall armyworm, native to tropical areas. The present work aims to present a discussion about the life cycle and protocols for rearing, in the laboratory, of S. frugiperda, in order to contribute as a didactic tool for the teaching of science and environmental education. For this, a bibliographic and scientometric survey was carried out from the MEDLINE/PubMed, Scientific Electronic Library Online (SciELO) and Google Scholar databases. The descriptors used were related to diet, feeding and rearing of S. frugiperda (Spodoptera frugiperda + artificial diet; Spodoptera frugiperda + laboratory; Spodoptera frugiperda + nutrition; Spodoptera frugiperda + larvae). As a result of the scientometric survey, 18 studies were selected, published between 1985 and 2022, on the topic, which reflects a wide variety of breeding protocols over time. The establishment of insect breeding protocols in the laboratory is essential for basic entomology studies, as well as for biotechnology and innovation studies involving, for example, insecticide bioassays. DOI:https://doi.org/10.56238/sevened2024.007-074